A STUDY ON ACEHNESE EFL LEARNERS’ PHONETICS: PRONUNCIATION ERRORS IN PRODUCING ENGLISH CONSONANT SOUNDS - Zalha, Fera Busfina; Lefiandi, Fachrizal (Getsempena English Education Journal, 2024)
With its distinct phonetic features, the correct pronunciation of the English consonant sounds has particularly been a challenge for EFL students, resulting them making errors in their pronunciation. The present study attempts to identify errors made by non-native students of English, especially Acehnese, in pronouncing English consonant sounds. Besides, the perceived factors causing the errors were also explored in order to demystify the potential reasons for the pronunciation difficulties. Using the frame of qualitative study approach, the current study gained the data through vocabulary tests and interviews. Five EFL learners of English language department of Universitas Islam Negeri Ar-Raniry Banda Aceh were selected as the participants of this study. The participants all represent Aceh Besar region only, to limit the findings, considering the possible effects of their mother tongue on their English pronunciation. The data were collected through vocabulary test and interview. This study found that the students experienced difficulties in producing the sounds [b], [d], [g], [v], [ʒ], [z], and [ʃ]. The data from the interview also reveal four perceived factors leading to the pronunciation errors including challenge in enunciating sounds with similar phonetical features, unawareness towards the correct pronunciations, mother tongue’s impacts towards English pronunciation, and lack of practice. This study’s findings contribute the field of EFL studies as correct pronunciation is emphasized in the mastery of the English language; thus, awareness on which sounds are difficult to pronounce and the factors causing the difficulties are essential for both EFL educators and learners.